Assessing “beneficiary” communities’ participation in HIV/AIDS communication through community radio - Siyasanga Tyali; Keyan Tomaselli (Communicare)
This article gives account of a research study that was conducted on a “beneficiary” community’s participation in HIV/AIDS communication through a community radio station. The aim was to understand the community’s presence and access to dialogue on HIV/AIDS, as practiced by their community radio station. The research underpinning the article focused on a community radio station based in Platfontein, Kimberley, in South Africa. X-K FM is a community radio station with !Xun and Khwe people as its primary target audience. The station is the only formal communication channel that targets these communities in their respective mother tongues. The researchers attempted to understand civil voices’ participation in and access to the strategies of HIV/AIDS prevention, care, support and treatment. The article is underpinned by Jürgen Habermas’s theory of structural transformation of the public sphere. Research data was gathered using semistructured interviews. The article concludes that the radio station has provided some avenues to facilitate the process of beneficiary community participation in HIV/AIDS communication.